Inheritance Of Children Through The Cloning Process The Perspective Of Civil Law: - Nadia, Haiza (Fakultas Syariah Univeritas Islam Madura, 2024)
Cloning in Positive law in Indonesia has not received a response from the lawmakers, perhaps because it is considered still not feasible in Indonesia. Even though if this embryo cloning process occurs, it can disrupt the existing legal order in Indonesia, such as the Marriage Law, Inheritance Law and others. The research method used is a qualitative research method that produces descriptive data in the form of writing from the observed research object. The type of research in this study is using library research, namely through a method that collects data by understanding and studying theories from various literature related to the object of research. The results show that cloning is a method of procreation without going through the asexual process, so it can be said to have similarities with attempts to conceive outside of natural means. This is the same as stated in Government Regulation No. 61 of 2014 concerning reproductive health contained in Article 40 verse (1) that assisted reproduction or pregnancy outside of natural means can only be carried out in married couples who are bound by a legal marriage and experience infertility to obtain offspring, Then verse (2) explains that it is carried out by using the results of fertilization of sperm and ovum originating from the husband and wife concerned and implanted in the womb of the wife from which the ovum originated. In addition, it is also stated that in carrying out assisted reproduction or pregnancy outside the natural way, it must be carried out in accordance with the development of science and technology.